International trade regulation : evolving dynamics and shifting foundations - Wang, Zhiqiong June; Chen, Jianfu (Routledge focus, 2023)
The international trade regulatory system is a dynamic system that has been evolving throughout its history. Tension and conflict are part of the system. While calls for the abolition of the principal trade regulation authority, the WTO, have failed to understand this nature of the system, proponents for reforms have so far not paid sufficient attention to the evolving nature of tension and conflict. This book examines the evolving dynamics in international trade regulation from the conclusion of GATT in 1947 to the current crisis facing the WTO, from a perspective of emerging powers of developing countries with a focus of China as the latest force that demands reforms of the international trade regulatory regime. There is an extensive body of scholarship on ideological struggles, the rise of developing countries, geopolitical contest, the emerging powers (especially China), the use, misuse or abuse of trading rules and so on. There is, however, a lack of a single concise research book that synthesises these underlying causes and factors into a coherent and precise analytical theme. This book attempts to fill this research gap by building upon the existing scholarship and placing the various tensions and conflicts in a perspective that treats them as dynamic factors that have propelled a continuing process of evolution of the international trade regulation. The book will interest those researching on international trade regulation as well as development studies. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non-Commercial-No Derivatives 4.0 license.